PEMBERDAYAAN MASYARAKAT DENGAN KETERPADUAN ANTARA SOSIALISASI UPAYA SANITASI DAN RESPON PELATIHAN PEMILAHAN SAMPAH DI SEKOLAH BERBASIS IT - Mulyati, Sri Slamet; Pujiono, Pujiono; Hidayah, Nurul; Nurjaman, Ujang; Herdhianta, Dhimas (Poltekkes Kemenkes Bandung, 2024)
Background: The activity of sorting waste is simple but requires awareness and commitment from the individual concerned. Scientific understanding in sorting is also needed to become a basis that can strengthen individual commitment and responsibility in handling waste. Public facilities whose sanitary conditions do not meet the requirements will be synonymous with slum and dirty conditions. Sanitation facilities and facilities that meet the requirements will certainly support the existence of healthy schools. Healthy schools are also one of the themes of community service that has been carried out by many community service teams in various educational institutions. Objective: This community service activity aims to find out efforts to improve soil environmental health, waste management, and find out the response to IT-based waste management in the school. Methods: Direct field surveys at school locations, conducting outreach, and demonstrations of IT-based tools are the methods used in our team's community service. Results: Soil quality at both school locations for pH and humidity parameters in the categories meets the requirements, indicating that there are no activities that have the potential to pollute the soil at these locations. Waste management efforts are already at the sorting and processing/composting stage which continues to be processed by partner 1. There is a positive response from both partners to the IT-based waste sorting tool. There was an increase in students' knowledge at both schools regarding waste sorting before and after the counseling. Conclusion: Environmental sanitation efforts and good IT-based training responses need to continue to be followed by good and sustainable waste processing practices..Key words: smart sorting bin, waste sorting